تعامل الليبراليين الإندونيسيين تجاه الآيات القرآنية : دراسة تحليلية - همة، إيتي ناجحة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The issue of liberal thought in the Qur'an is one of the most significant topics which are covered by the Indonesian Muslim scholars and thinkers. They came out with interpretation of the Qur'anic verses on the fundamental issues of Islam with the use of liberal approach and put its meaning not in appropriate manner. The purpose of this study is to explore the verses of the Qur'an which are interpreted by the Indonesian Muslim thinkers and the methodological framework they used to interpret those verses, and to present a critical and analytical toward their views comparing with interpretations of classical and contemporary exegetes. This research is based on three approaches: inductive, analytical, and critical approach. The most substantial findings of this research are: First, Qur'anic interpretation in the hands of Indonesian Muslim liberal thinkers pertaining to theological concept (al-aqidah), Islamic Shariah, and moral precepts. With regard to theological concept, we refer to Surah Al-Baqarah 62, Surah Al- Kāfirūn 1-6, while the aspect of Islamic Shariah we refer to Surah Al-Ahzab 59, and Surah Al-Baqarah 221; and the moral precepts can also be referred to Surah Al-A'rāf 81, and Surah Al-Nūr 31. In addition, we came out with the findings in which Muslim liberal thinkers in dealing with the Qur'anic verses they employ it what so-called sociocultural analysis, semiotic and literal analysis, and scientific approach. It can be sum up that interpretation of the Indonesian Muslim liberal thinker is baseless from the language, Shari'ah and religious angles. It can be claimed that their interpretation is against the whole coverage of verses and even can be regarded as distortion. Hence, Muslims take extra precaution and remain alert on such kind of tendencies in dealing with the Qur'anic verses.